2016
DOI: 10.1002/jsfa.7489
|View full text |Cite
|
Sign up to set email alerts
|

Health benefit of fucosterol from marine algae: a review

Abstract: Seaweeds belong to a group of marine plants known as algae, which are consumed as sea vegetables in several Asian countries. Recent studies have focused on the biological and pharmacological activities of seaweeds and their highly bioactive secondary metabolites because of their potential in the development of new pharmaceutical agents. Although several varieties of bioactive novel compounds such as phlorotannins, diterpenes and polysaccharides from seaweeds have already been well scrutinized, fucosterol as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(75 citation statements)
references
References 86 publications
(134 reference statements)
0
73
0
1
Order By: Relevance
“…Older analytical techniques may have misidentified algal sterols as cholesterol since their structures are similar (Pereira et al 2016). Fucosterol occurs in many algae, especially red and brown macroalgae (Pereira et al 2016), and this compound may have value in treating complications of diabetes and hypertension, as well as other major health concerns (Abdul et al 2016). However, like other studies of algal foods, the linkages are implied but little is known about the actual in vivo effects of fucosterol when algae are consumed by humans.…”
Section: Lipidsmentioning
confidence: 99%
“…Older analytical techniques may have misidentified algal sterols as cholesterol since their structures are similar (Pereira et al 2016). Fucosterol occurs in many algae, especially red and brown macroalgae (Pereira et al 2016), and this compound may have value in treating complications of diabetes and hypertension, as well as other major health concerns (Abdul et al 2016). However, like other studies of algal foods, the linkages are implied but little is known about the actual in vivo effects of fucosterol when algae are consumed by humans.…”
Section: Lipidsmentioning
confidence: 99%
“…Ecklonia stolonifera (brown algae) is widely distributed along the middle Pacific coast around Korea and Japan. Recently, several researches have reported that E. stolonifera possesses beneficial bioactivity, such as the prevention of diabetic complications, and anticholinesterase, antihyperlipidemic, anti‐inflammatory, antiskin ageing, tyrosinase‐inhibitory and hepatoprotective activity . Fucosterol is a sterol metabolite of E. stolonifera, and its anti‐adipogenic activity has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…supports that the concentration of fucosterol in Laminaria japonica , brown seaweed, gets its maximum during winter period, which decreases in autumn. It is well‐known that fucosterol exhibits various biological activities including anticancer, antioxidant, antihyperlipidemic, blood cholesterol reducing and blood vessel thrombosis preventive . It was reported that the sterol composition in green algae, is complex and differs than in other groups of algae .…”
Section: Resultsmentioning
confidence: 99%